THE HUMAN BEING'S RIGHT TO LIVE IN A HEALTHY ENVIRONMENT (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Today’s world faces with a real problem, what people call “ecological crisis” which has become a very debate topic in the national and international conferences such that, more and more, scientists, theologians and politicians started to be alert that the creation is not eternal if it is not preserved and protected. The whole creation should be seen as the home for living beings and the context for God’s Incarnation and humankind’s deification. But this creation’s purpose is closely related by human beings’ intention, to their desire to grow up spiritually, to dialog with God, seeing creation as a bridge between them, between the uncreated and the creation. Thus the importance of the human being becomes crucial for the return of gift to its Giver, the Trinitarian God. Because creation has a beginning and it has been made it stays in existence only in relation with a personal God who manifests his love upon. The presence of God’s love in creation leads us to the idea that the world has not been created from an inner necessity of Creator. Creation is not a sign of lack; it is an expression of the profusion of God’s love that is not a selfish love. This is a love that creates a real dialog between Creator and creatures and which involves creation as a space where the meting between transcendence and immanence, sensible and intelligible takes place. Therefore, the material world can be seen as a gift of a Person. Thus when creation is regarded as a gift, the people’s knowledge will not remain only to the visible objects and creation will not become an idol. If creation is reduced at proper immanence, it will be in danger of extinction because its final purpose is disappeared and God (Giver) will be reduced to a concept; God will not be the accessible subject of the experience any more. People through their work complete the creation creatively and bring it to God. Thus creation is taken out of its bondage of creature and is transfigured in “a new heaven and a new earth…” (Revelation 21,1), being in communion with its Giver, source of existence: “For lo, those who are far from thee shall perish…” (Psalm 73,27).